Nanocrystal TiO2 Engulfed SiO2-Barium Hexaferrite for Enhanced Electrons Mobility and Solar Harvesting Potential - Azrina, Abd Aziz; Shaliza, Ibrahim; Pichiah, Saravanan (Trans Tech Publications, Switzerland, 2015)
Barium hexaferrite embedded-silica-titania photocatalyst (TiO2-SiO2-BaFe12O19) was synthesized through sol-gel, liquid catalytic phase transformation and solid reaction routes. The magnetic photocatalyst was aimed to harvest the photoenergy from the sunlight, minimize the electron-holes recombination rate, improve the long lifetime charge-carriers transfer to maximize the photocatalytic activity and enhances the separation and reusability of it. The as-synthesized photocatalyst was characterized and the photocatalytic activity was evaluated for the reduction of 2, 4-dichlorophenol (2, 4-DCP) under direct sunlight. The presence of SiO2 interlayer in TiO2-SiO2-BaFe12O19 prevents the phase transformation of magnetic core. TiO2-SiO2-BaFe12O19 benefits the magnetic separation with appreciable magnitude of coercivity (5035.6 Oe) and saturation magnetization (18.8256E-3 emu/g), respectively. The ferrite ions from the magnetic core which dispersed into TiO2 matrix exhibited an evident shift of the absorption in the visible region. This was again confirmed with the reduced band gap energy of 1.90 eV. Furthermore, TiO2-SiO2-BaFe12O19 destructed 100% of 2, 4-DCP compound within 150 min under very bright sunlight with an average irradiance of 820.8 W/m2 (results not shown). The embedding of BaFe12O19 with a SiO2 layer onto TiO2 nanocrystals contributed for an excellent solar-light utilization and ease magnetic separation of the nanosized photocatalyst.